Biosynthesis inhibition of miR-142-5p in a N 6-methyladenosine-dependent manner induces neuropathic pain through CDK5/TRPV1 signaling - Jinshi Li; Yang Guo; Chen Zhu; Dongxu Wang; Yuan Li; Xiaotong Hao; Linyan Cao; Yiting Fan; Bo Fang (Cellular & Molecular Biology Letters)
Abstract Background Neuropathic pain (NP) represents a debilitating and refractory condition. However, the understanding of NP and the current treatment approaches available for its management are limited. Therefore, there is a significant need to address the dearth of effective therapeutic interventions. This study aims to investigate the regulation of transient receptor potential vanilloid 1 (TRPV1) and cyclin-dependent kinase 5 (CDK5) expression levels by miR-142-5p as a common upstream molecule, and to delve into the mature process of miR-142-5p from the perspective of N 6-methyladenosine (m6A) modification. Methods To assess the RNA levels of TRPV1, CDK5, miR-142-5p, pre-miR-142, and pri-miR-142, quantitative PCR with reverse transcription (RT–qPCR) was utilized. Western blot analysis was employed to determine changes in protein expression for TRPV1 and CDK5. For assessing the interaction mechanism and binding site between TRPV1 and CDK5, various techniques were applied, including mass spectrometry, coimmunoprecipitation (co-IP), and glutathione-S-transferase (GST)-pulldown assays. The subcellular localization of TRPV1 on the cell membrane was visualized through immunofluorescence, and the translocation was confirmed by western blot analysis after performing membrane-plasma separation in parallel. Moreover, intracellular calcium transport was monitored using calcium imaging as an indicator of cell excitability. The binding of miRNA-142-5p to the 3’UTR of TRPV1 and CDK5 was investigated using the dual-luciferase reporter assay. The overall level of m6A was first determined by RNA m6A methylation assay, and subsequently the methylation level of pri-miR-142 was assessed using the meRIP assay to detect m6A modification. In addition, an in vivo rat chronic constriction injury (CCI) model was established, and miR-142-5p agomir or antagomir was injected intrathecally. An enzyme-linked immunosorbent assay (ELISA) was used to measure the levels of IL-6 and TNF. Paw withdrawal mechanical threshold (PWMT) and paw withdrawal thermal latency (PWTL) were examined. Results The expression levels of TRPV1 and CDK5 were found to be upregulated not only in the in vivo CCI model but also in the in vitro lipopolysaccharide (LPS) treatment cell model as well. CDK5 was observed to phosphorylate TRPV1 at T406, prompting the translocation of TRPV1 to the cell membrane and consequent augmentation of cellular excitability. Notably, CDK5 was found to directly bind to TRPV1, and the binding region was localized within the 1–390 amino acid sequence of TRPV1. According to database predictions, miR-142-5p, identified as a shared upstream molecule of TRPV1 and CDK5, exhibited downregulation following induction by NP. MiR-142-5p was shown to simultaneously bind to the mRNA of CDK5 and TRPV1, thereby inhibiting their expression. After LPS treatment, it was observed that pri-miR-142 expression increased, while pre-miR-142 and miR-142-5p expression decreased, suggesting inhibition of the maturation process of pri-miR-142. In addition, the overall level of m6A and in particular the pri-miR-142 m6A modification increased upon LPS treatment. Knockdown of METTL14 led to decreased pri-miR-124 expression, increased pre-miR-124 expression, and enhanced mature miR-142-5p expression, indicating the relief of miR-142-5p maturation repression. The in vivo results indicated that miR-142-5p negatively regulated the expression of CDK5 and TRPV1, suppressed the expression of inflammatory factors IL-6 and TNF, and improved the PWMT and PWTL. Conclusions In this study, we perform a thorough investigation to examine the effects of CDK5 and TRPV1 on NP, elucidating their binding relationship and the impact of CDK5 on the membrane transport of TRPV1. Notably, our findings reveal that miR-142-5p, acting as a crucial upstream molecule, exhibits inhibitory effects on the expression of both CDK5 and TRPV1. Moreover, we observe that METTL14 facilitates the m6A modification of pri-miR-142, thereby impeding the maturation transition of pri-miR-142 and ultimately leading to the downregulation of mature miR-142-5p. Graphical Abstract